Oral versus intravenous sildenafil for pulmonary hypertension in neonates: a randomized trial - Chinmay Chetan; Pradeep Suryawanshi; Suprabha Patnaik; Naharmal B. Soni; Chandra Rath; Prince Pareek; Bhvya Gupta; Reema Garegrat; Arjun Verma; Yogen Singh (BMC, 2022)
Abstract Background Sildenafil is the drug of choice for neonatal pulmonary hypertension in developing countries where inhaled nitric oxide is not available. Available as oral and intravenous preparation - no study has been done in the past to compare the two forms. Each has its own benefits - but requires comparison in terms of efficacy and safety. This study was done to compare the efficacy of oral versus intravenous (IV) sildenafil in infants with mild to moderate pulmonary hypertension. Methods An open labelled randomized trial was conducted in a neonatal intensive care unit of urban tertiary hospital in western India between February 2019 to December 2020. Infants born after 34 weeks of gestation with Pulmonary arterial pressure (PAP) > 25 mm Hg measured by echocardiography, within 72 h of birth, were enrolled for the study. Participants were randomly assigned to receive sildenafil either orally or by intravenous route. Primary outcome was the time taken for PAP to decrease below 25 mm Hg. Secondary outcomes were time taken for oxygenation index to decrease by 25%, duration of invasive and non-invasive mechanical ventilation, nasal oxygen, hospital stay, time to achieve full feeds, mortality, and side effects. Results Forty patients were enrolled. The baseline characteristics of neonates in both groups were similar except for APGAR scores at 1 min and 5 min, with oral group having lower score [MEDIAN (IQR) 5.00 (4.00- 7.00) and 7.00 (6.00- 8.00)] compared to IV group [MEDIAN (IQR) 7.00 (6.00-8.00) and 9.00 (8.00-9.00)] respectively. Time taken for PAP to decrease below 25 mm was not statistically different between the oral and intravenous groups. Systemic hypotension occurred in 4 neonates of the intravenous group but none in the oral group. Conclusion Oral and intravenous sildenafil had equal efficacy at reducing PAP in neonatal pulmonary hypertension, albeit intravenous sildenafil use was associated with a greater complication rate. Trial registration Trial was registered in the clinical trials registry of India [ CTRI/2019/04/018781 ][25/04/2019].